Closed‐Loop Dynamically Adaptive Educational Systems. (13th September 2022) - Wade, Jon; Dow, Steven; Gerardo, Hortense; Gessner, Richard; Hargis, Jace
Abstract: We believe that our education systems are currently not capable of evolving at the rate necessary to meet the challenges presented by rapidly changing technology epitomized by Industry 4.0 and the digital transformation. Our research project goal is to pilot a learning laboratory that can be used to conduct the necessary experiments to create and apply the foundational knowledge necessary to support a dynamically adaptive educational system for university students that can meet the challenges presented by rapid change. Our research will address the following three critical areas: educational program evolution, social real‐time learning, and personalized knowledge discovery. This paper describes how these three research tracks will produce generalized knowledge about feedback mechanisms that can serve as a foundation for the creation of a dynamic, self‐adapting educational system impacting individual students' acquisition and application of knowledge, skills and dispositions as well as classroom curricula and pedagogy, and program outcomes and design.